Rudiments 1, 2 & 3: Design Speculations on Autonomy - Helmes, John; Taylor, Alex; Cao, Xiang; Höök, Kristina; Schmitt, Peter; Villar, Nicolas (Proceedings of the fifth international conference on Tangible, embedded, and embodied interaction, TEI '11, 2011)
This work describes the design process and installation of three speculative, rudimentary machines, or rudiments. Through careful iterations in their design, the rudiments are intended to provoke curiosity and discussion around the possibility of autonomy in interactive systems. The design of the rudiments is described in detail, alongside the design decisions that were made to suggest a machine autonomy and to provoke discussion. Some preliminary reflections from installing the rudiments in two separate households are also reported. Widely divergent opinions of the rudiments from the two households are used to discuss a number of themes for thinking about autonomy and interactive systems design. Overall, the presented work adopts a perspective strongly oriented towards guiding future research, but, importantly, aims to do so by opening up and exposing the design possibilities rather than constraining them.